A stable LaB6 nanoneedle field-emission point electron source. Issue 10 (21st April 2021) - Tang, Shuai; Tang, Jie; Uzuhashi, Jun; Ohkubo, Tadakatsu; Hayami, Wataru; Yuan, Jinshi; Takeguchi, Masaki; Mitome, Masanori; Qin, Lu-Chang
Abstract : A LaB6 nanoneedle that is fabricated using a focused ion beam shows a high reduced brightness, small energy spread, and especially high emission stability. It can now be used practically as a next-generation field-emission point electron source. Abstract : A material with a low work function exhibiting field-emission of electrons has long been sought as an ideal point electron source to generate a coherent electron beam with high brightness, long service life, low energy spread, and especially stable emission current. The quality and performance of the electron source are now becoming limiting factors for further improving the spatial resolution and analytical capabilities of the electron microscope. While tungsten (W) is still the only material of choice as a practically usable field emission filament since it was identified more than six decades ago, its electron optical performance remains unsatisfactory, especially the poor emission stability (>5% per hour), rapid current decay (20% in 10 hours), and relatively large energy spread (0.4 eV), even in an extremely high vacuum (10 −9 Pa). Herein, we report a LaB6 nanoneedle structure having a sharpened tip apex with a radius of curvature of about 10 nm that is fabricated and finished using a focused ion beam (FIB) and show that it can produce a field emission electron beam meeting the application criteria with a high reduced brightness (10 10 A m −2 sr −1 V −1 ), small energy spread (0.2 eV), and especially high emission stability (<1% fluctuation in 16 hours without decay). It can now be used practically as a next-generation field-emission point electron source.